Effect of Intravenous Tirofiban Versus Placebo on Excellent Outcome in Patients With Acute Ischemic Stroke: The Multicenter, Randomized INSTANT Trial Protocol - Fan Zhang; Minghui Xiao; Cong Zhang; Guangxiong Yuan; Zhiyong Xie; Yi Yin; Ruize Zhou; Shanggui Yuan; Genxiang Xiao; Donghuan Mei; Xiaobing Zeng; Huashi Liu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background It is common that symptoms do not improve or even worsen after intravenous thrombolysis (IVT) in acute ischemic stroke. However, it remains unknown whether early administration of tirofiban after IVT may improve clinical outcomes. This trial aims to assess the efficacy and safety of early administration of tirofiban after IVT with tenecteplase in acute ischemic stroke during the 90‐day follow‐up period after treatment. Methods The INSTANT (Intravenous Tenecteplase and Tirofiban for Acute Ischemic Stroke) trial is an investigator‐initiated, randomized, placebo‐controlled, double‐blind, multicenter trial. In the study, 310 patients with acute nonlarge/medium‐sized vascular occlusion and nonatrial fibrillation stroke who are treated with intravenous tenecteplase will be consecutively randomized to intravenous tirofiban or placebo in a 1:1 ratio over 2 years across 50 intravenous thrombolysis‐capable stroke centers in China. In addition, eligible subjects will receive best medical treatment according to national guidelines. The primary efficacy end point is excellent functional status, defined as a score of 0 or 1 on the modified Rankin Scale at 90 days after randomization. Safety outcomes include symptomatic intracranial hemorrhage within 48 hours and mortality at 90 days. Conclusions The INSTANT trial was designed to determine the role of tirofiban within 24 hours after IVT in patients with acute ischemic stroke. Our primary objective is to investigate whether the early administration of tirofiban following IVT can enhance the proportion of patients exhibiting no or minimal symptoms post acute ischemic stroke. Registration URL: ChiCTR2300074368; Unique Identifier: www.chictr.org.cn.